Phylogenetic Characteristics of West Nile Virus Isolated From Culex modestus Mosquitoes in West Kazakhstan - Nurmakhanov, Talgat; Sansyzbaev, Yerlan; Atshabar, Boris; Berlin, Vladimir; Kobzhasarov, Damir; Yeskhojayev, Olzhas; Vilkova, Anna; Ayazbayev, Timur; Andryuchshenko, Alexey; Bidashko, Fyodor; Hay, John; Shvetsov, Alexandr (Frontiers in Public Health, 2021)
West Nile virus (WNV) is widespread in southern Russia, where the fever appears annually. Since West Kazakhstan borders on southern Russia, we examined mosquitoes in the is region for the presence of WNV. Virus was detected in Culex modestus and isolates are related to strains from Volgograd, Russia. A screen for seroconversion to the virus (IgG) was conducted and approximately 5% of the local population tested positive.